Peningkatan Hasil Belajar Siswa Kelas VII SMP Kristen Tounwawan Pada Materi Persamaan Dan Pertidaksamaan Linear Satu Variabel Dengan Menggunakan Model Pembelajaran Kooperatif Tipe STAD - Samurwaru, Jubel Ernawaty; Molle, Juliana S; Tamalene, Hanisa (Sora Journal of Mathematics Education, 2022)
This study aims to determine the improvement of student learning outcomes on the material of one-variable linear equation and inequalities system by applyning the cooperativ types STAD model. The subjects in the study were all eighth grade students of SMP Kristen Tounwawan with a total of 25 students. This research is a Classroom Action Research with the teacher acting as a teacher acting as a teacher and lasts for 3 cycles. Data was collected using tests and observations. The data analysis technique uses quantitative analysis and quantitative analysis. The results of the analysis showed that there was an increase in student learning outcomens from the first cycle, 20% (5 students) who achieved the KKM 60 to the second cycle 48% (12 students) who reachd the KKM 60 and the cycle, 100% (25 students) who reach KKM . From the results obtained, the coopeative learning model of the material of a two-variable linear equation system.